8(x-4)-1=6x+1

Simple and best practice solution for 8(x-4)-1=6x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(x-4)-1=6x+1 equation:


Simplifying
8(x + -4) + -1 = 6x + 1

Reorder the terms:
8(-4 + x) + -1 = 6x + 1
(-4 * 8 + x * 8) + -1 = 6x + 1
(-32 + 8x) + -1 = 6x + 1

Reorder the terms:
-32 + -1 + 8x = 6x + 1

Combine like terms: -32 + -1 = -33
-33 + 8x = 6x + 1

Reorder the terms:
-33 + 8x = 1 + 6x

Solving
-33 + 8x = 1 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-33 + 8x + -6x = 1 + 6x + -6x

Combine like terms: 8x + -6x = 2x
-33 + 2x = 1 + 6x + -6x

Combine like terms: 6x + -6x = 0
-33 + 2x = 1 + 0
-33 + 2x = 1

Add '33' to each side of the equation.
-33 + 33 + 2x = 1 + 33

Combine like terms: -33 + 33 = 0
0 + 2x = 1 + 33
2x = 1 + 33

Combine like terms: 1 + 33 = 34
2x = 34

Divide each side by '2'.
x = 17

Simplifying
x = 17

See similar equations:

| 0.95x^2-15x+20=0 | | 0.1a-0.3=0.2a-8.3 | | 6y^2+4= | | -6.04-2.9c=2.6(c+3.6) | | -5-y-1=9 | | 7a-14=15(a-6) | | (x)ln(3)=(2)-(x)ln(2) | | 4=m+11 | | 6x-3=9y | | 3.7x+42=-5.2x+9 | | x^4+7x^2-6=0 | | x^4+7x^2-6x=0 | | 3x-4(x+1)+8=0 | | 9y-2=7+11y | | 6-x=2x | | 7(2x-6)+3=3(2x+1)+2(4x-5) | | 236=0+n | | c^2=12 | | 8.6t+3.34=-51.70 | | b^2=18 | | 4w=68 | | .6y-6=2 | | x*ln(3)=2-x*ln(2) | | 0.02x-1.56=0.8x | | x-34=72 | | 14=.6(9y-15) | | 10c=260 | | 3(2a-6)=34 | | 9h=207 | | 34(19-5.5x)=16(5x-8)+53.1 | | 7g=91 | | 32=.5x(x+12) |

Equations solver categories